Look left, look right, but it is mostly just straight ahead. Issue 2 (1st February 2016) - Butman, Samuel M.
Key Points: Predicting the likelihood of side branch occlusion is possible. Guaranteeing side branch patency without procedural stenting, not so much. Wouldn't a randomized multicenter trial to define when to "pretreat, " let alone "post‐treat" the side branch and its impact, if any, on immediate‐ and long‐term outcomes be most excellent?